Book of Abstracts of the International Conference North Atlantic Security and Defense Strategy (NASDS 2022), 19-20 May 2022, Military University Institute, Lisbon, Portugal - Marsili, M. (2022)
This book contains the abstracts accepted for presentation, after a peer-review process, at the international conference North Atlantic Security and Defense Strategy (NASDS 2022), held on May 19-20, 2022 at the Military University Institute, Lisbon. The conference was organized by the Center for Research and Development of the Military University Institute/General Staff of the Armed Forces (Portugal) in cooperation with the Institute of International and European Law of Reykjavík University (Iceland), and the Centre for Security Policy of the Norwegian Institute for Defence Studies (Norway). The conference gathered scholars, experts and practitioners, especially from Arctic countries, EU and NATO member states. The conference, aimed to broaden the debate on the security and defense in the North Atlantic and Arctic region, has the purpose to raise awareness on current pressing global challenges, and provide opportunities for researchers to share views that will enhance the future of the Euro-Atlantic and collective security.